Dendrimer-Mediated Transdermal Formulation of Luliconazole: A Promising Approach for Enhanced Delivery - Yadav, Janhavi (Journal of Biomedical and Pharmaceutical Research, 2023)
The present study aimed to develop the PAMAM dendrimer-mediated transdermal formulation of luliconazole. Luliconazole has anti-fungal activity. It acts by inhibiting lanosterol demethylase, which is a major component of the fungus cell wall. Luliconazole has a melting point of 150-152°C and is soluble in various solvents. Its lipophilicity is 4.16 in n-octanol. UV spectroscopy shows no significant interaction with polymers. Calibration curves are linear in 1-10 µg/ml. Solubilization studies show that luliconazole exhibits pH-dependent solubility, increasing with increasing pH. The drug’s solubility is affected by dendrimer concentration and pH, with a pKa of 4.15. Dendrimers offer several advantages over conventional polymers concerning drug interactions, including that they are well-defined molecules, allow the development of well-defined drug/polymer systems, and have the potential for high drug payloads. In addition to increasing the solubility, PAMAM dendrimers offer the possibility for sustained release of the drug from the drug-dendrimer complex. They also provide the possibility to design pH-dependent controlled release drug delivery systems containing the drug trapped inside the dendrimers. The present research study is to develop the PAMAM dendrimer-mediated transdermal formulation of luliconazole and explore the potential of PAMAM dendrimer as a noval drug delivery to enhance skin permeation Keywords: Dendrimer-Mediated, Transdermal Formulation, Luliconazole,PAMAM.